Identification of novel indole derivatives acting as inhibitors of the Keap1–Nrf2 interaction. (1st January 2019) - Cosimelli, Barbara; Greco, Giovanni; Laneri, Sonia; Novellino, Ettore; Sacchi, Antonia; Amendola, Giorgio; Cosconati, Sandro; Bortolozzi, Roberta; Viola, Giampietro
Abstract: Nine indole derivatives (9a-i ) were tested as potential inhibitors of the Keap1–Nrf2 interaction. This class of compounds increases the intracellular levels of the transcription factor Nrf2 and the consequent expression of enzymes encoded by genes containing the antioxidant response element (ARE). In the ARE-luciferase reporter assay only 9e -g revealed to be remarkably more active than t -butylhydroxyquinone ( t -BHQ), with 9g standing out as the best performing compound. While 9e and 9f are weak acids, 9g is an ampholyte prevailing as a zwitterion in neutral aqueous solutions. The ability of 9e-g to significantly increase levels of Nrf2, NADPH:quinone oxidoreductase 1, and transketolase (TKT) gave further support to the hypothesis that these compounds act as inhibitors of the Keap1–Nrf2 interaction. Docking simulations allowed us to elucidate the nature of the putative interactions between 9g and Keap1. GRAPHICAL ABSTRACT: